A Study of Daily Living Dependency Status among Elderly in an Urban Slum area of Dehradun - Ohri, Puneet; Gupta, Sudhir Kumar; Upadhyai, Neha (Indian Journal of Community Health, 2014)
Background: Population aging is observed world-wide. As per Census 2011, elderly constitutes 7.4% population of India. It is expected to increase to 20% in 2050. This segment of population faces multiple medical and psychological problems. To address and solve these problems great effort from the country and the community is required. Objective: To assess the daily living dependency status among elderly. Method: A cross sectional study was conducted in Dehradun, among 215 elderly people, using a pre-structured questionnaire. Their activities of daily living (ADL) and Instrumental activities of daily living (IADL) were recorded by observation and interviewing them with their families. Results: Out of total, 93% individuals were independent in their ADLs, with more dependence in the very old elderly. Maximum inability was found in Bathing and dressing. 70.7% elderly were dependent on one or more IADLs, female elderly being more dependent than male (p<0.05). However there was no significant difference of dependence in the male and female elderly in performing ADLs. Education and socio-economic status had a positive effect on independence in IADLs. Among all IADLs male elderly showed a maximum dependency for cooking and laundry while females showed a greater dependency in using telephone, managing money and travelling.